Appearance of Subjectivity - B. Bratina; S. Bratina (Концепт: философия, религия, культура, 2021)
The authors attempt to outline an ontological perspective different from the mainstream materialistic ontology. Some aspects of this perspective can be found in the works of eminent philosophers of the past, such as Husserl or Hegel. The authors, however, point out a systematic methodological mistake earlier thinkers made concerning the notion of the Other. The Other is the key factor in the development of consciousness and subjectivity, and this paper seeks to show how the Other moulds and creates subjectivity out of a biological man. Human identity arises in two steps: ontological identity is  created first, from which empirical identity grows, culminating in consciousness and personality. It was logical for philosophical consciousness to contemplate subjectivity which is not yet formed. Tabula rasa is a  biological man, but that structure will not become a human subjectivity if it  does not dwell with other subjectivities. The Other is not simply another Self. There is no elementary sensation to inform a biological organism of the state in which it finds itself; it is a kind of a physical unity for the emerging  consciousness, but in itself it is not yet ready to perceive and act according to it at this stage. Without the influence of the Other, a human organism will never become Self. This unifying perception of the Other depicts an original encounter where there is also fascination. But fascination turns into  frustration when the Other disappears or exits the focused perceptual field. This process of perceptual addition and dissolution is repeated, creating a change in what can be called the game of presence and absence. With the departure of the Other, the cause of the focus goes away, but what remains  is its trace — the attention that is now left to wonder. Attention left without  its source is only to itself and is directed to itself because this is the only direction that remains. Subjectivity, once symbolised by a circle, finally takes the form of a torus in whose interior hole resides the trace of the Other. With  the entry of multiple Others into the relationship, primarily through speech, meanings acquire solid aspects introducing the law of symbolic order. This stabilisation of meanings frees uninitiated subjectivity, by which  one truly enters the field of freedom opening that of ethics. The authors’ point is that accounting for the notion of external world, one should consider the Other first, and only after that simple otherness.